Consumer Motivation, Information Earning, and Evaluation of Attributes of Premium Handbag in Jakarta - Adhitama, Ergy; Hudrasyah, Herry (Journal of Business and Management, 2012)
Purpose: The paper aims to explore motivation, information earning, and evaluation of attributes that influence consumer in Jakarta to buy and use premium handbag.Design/methodology/approach: This study answers the problems using the secondary data to develop the research. In depth interview to key informants is also done to get detail and deep information around the phenomenon. Result of interview is used for develop survey process with judgment sampling to 188 women who had ever bought and used premium handbag in Jakarta. Descriptive and factor analysis was used to process the data collected.Â Findings: Descriptively, design strongly motivates consumers in Jakarta. Friend is the most influential source according to consumers in Jakarta.. Color is the most considered attribute before buy and use premium hand bag in Jakarta.Â Research limitations/implication: Future research is suggested to research the marketing strategy based on result of this study regarding to motivation, information earning, and evaluation of attributes of premium handbag consumers in Jakarta.Â Practical implication: The marketing strategy implied to premium handbag product category has to touch the emotional side of consumers in order to makes consumer gain appropriate perceived value in possessing handbag.Originality/value: This paper answers what is behind the possession of premium handbag in Jakartam regarding to motivation, information earning, and evaluation of attributes.Keywords: Keyword: Motivation, Information Earning, Evaluation of Attributes, Premium Handbag